Kościół Polskokatolicki i Samodzielne Niezależne Parafie Rzymskokatolickie w polityce wyznaniowej państwa polskiego po 1956 roku: źródła do sprawy Gądkowa Wielkiego = The polish state's post -1956 policy towards the Polish Catholic Church and the independent autonomic roman catholic parishes: the case of Gądków Wielki - Michalak. Ryszard (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Stalinist repression policy towards minority denominations was aimed at their ultimate obliteration. Although it was stopped in October'56, the resulting state-dependence of some of the Churches - including the Polish Catholic - continued.While most Churches quietly acquiesced in having to join the state's propaganda work, often against the Roman Catholics, the Polish Catholic Church under bishop Maksymilian Rode became a choice weapon in fighting the Roman Catholic Church.
Keywords: kościół polskokatolicki; kościół katolicki; stosunki państwo-kościół; polityka wyznaniowa; Polska - historia - od 1944 r.